Multimodal Signals: Cognitive and Algorithmic Issues COST Action 2102 and euCognition International School Vietri sul Mare, Italy, April 21-26, 2008, Revised Selected and Invited Papers - Esposito, Anna; Hussain, Amir; Marinaro, Maria; Martone, Raffaele (Lecture Notes in Artificial Intelligence, 2009)
This book constitutes the thoroughly refereed post-conference proceedings of the COST Action 2102 and euCognition supported international school on Multimodal Signals: "Cognitive and Algorithmic Issues" held in Vietri sul Mare, Italy, in April 2008. The 34 revised full papers presented were carefully reviewed and selected from participants' contributions and invited lectures given at the workshop. The volume is organized in two parts; the first on Interactive and Unsupervised Multimodal Systems contains 14 papers. The papers deal with the theoretical and computational issue of defining algorithms, programming languages, and determinist models to recognize and synthesize multimodal signals. These are facial and vocal expressions of emotions, tones of voice, gestures, eye contact, spatial arrangements, patterns of touch, expressive movements, writing patterns, and cultural differences, in anticipation of the implementation of intelligent avatars and interactive dialogue systems that could be exploited to improve user access to future telecommunication services. The second part of the volume, on Verbal and Nonverbal Communication Signals, presents 20 original studies devoted to the modeling of timing synchronisation between speech production, gestures, facial and head movements in human communicative expressions and on their mutual contribution for an effective communication.